Motivational and evolutionary aspects of a physical exercise training program: a longitudinal study - Rosa, João P. P.; de Souza, Altay A. L.; de Lima, Giscard H. O.; Rodrigues, Dayane F.; de Aquino Lemos, Valdir; da Silva Alves, Eduardo; Tufik, Sergio; de Mello, Marco T. (Frontiers in Psychology, 2015)
Several studies have indicated that motivational level and prior expectations are relevant aspects to increase commitment to physical activity. Moreover, these aspects are not properly described in terms of proximal (Self Determination Theory) and distal (evolutionary) explanations in the literature. This paper aims to verify if level of motivation (BREQ-2) and expectations regarding regular physical exercise (IMPRAF-54) before starting a one-year exercise program could determine likelihood of completion. Ninety-four volunteers (53 women) included a completed protocol group (CPG n=21) and drop-out group (DG n=73). The IMPRAF-54 scale was used to assess six different expectations associated with physical activity, and the BREQ-2 inventory was used to assess the level of motivation in five steps (from amotivation to intrinsic motivation). Both questionnaires were assessed before the regular exercise program. The CPG group presented higher sociability and lower pleasure scores according to IMPRAF-54 domains. A logistic regression showed that a one-point increment on sociability score increased the chance of completing the program by 10%, and the same one-point increment on pleasure score reduced the chance of completing the protocol by 16%. ROC curves were also calculated to establish IMPRAF-54 cutoffs for adherence (Sociability - 18.5 points – 81% sensibility/50% specificity) and dropout (Pleasure – 25.5 points – 86% sensibility/20% specificity) of the exercise protocol. Our results indicate that an expectation of social interaction was a positive factor in predicting adherence to exercise. Grounded in SDT and its innate needs (competence, autonomy, relatedness), physical exercise is not an end; it is a means to achieve autonomy and self-cohesion. The association of physical activity with social practices, like in hunter-gathering groups, can engage people to be physically active and can provide better results in adherence exercise programs for the general population.